Analisis Prediksi Mahasiswa Terhadap Kelulusan Tepat Waktu Menggunakan Metode Data Mining Decision Tree (Studi Kasus: FTI UKSW) - Imelda Ruwae Lutunani; Adi Nugroho (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
In general, students have the responsibility to complete their studies at a university. For students of the Satya Wacana Christian University Faculty of Information Technology, which every year there are more and more students, the world of work is currently required to become someone who masters the field of technology. In addition, as a student, there are many things that must be done to complete studies by participating in activities on campus, organizations, and being active in the teaching and learning process so that they can complete their studies on time. In this study, a predictive analysis of SWCU FTI students will be conducted on timely graduation using the decision tree data mining method. which will see students who graduate on time and graduate late using the decision tree algorithm which is a decision tree algorithm that has a high level of accuracy in large amounts of data. In this study, the decision tree algorithm was used to run 983 sample data, resulting in a match accuracy of 91.25%. This means that it is very good and effective in predicting student graduation